2012
DOI: 10.5812/aapm.2629
|View full text |Cite
|
Sign up to set email alerts
|

Caudal Additives Do Not Improve the Analgesia Afforded by Levobupivacaine After Hypospadias Repair

Abstract: The addition of clonidine and/ or S (+)-ketamine to caudal analgesia does not appear to offer additional benefits for children undergoing hypospadias repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…On the other hand pain intensity is in direct association to inflammatory system activity and cytokines levels which create complications in patients; however, pain relief can result in very good results ( 2 ). Therefore pain management, as one of the main factors of postoperative care, has always been noteworthy to anesthesiologists ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand pain intensity is in direct association to inflammatory system activity and cytokines levels which create complications in patients; however, pain relief can result in very good results ( 2 ). Therefore pain management, as one of the main factors of postoperative care, has always been noteworthy to anesthesiologists ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different tools are recommended according to the verbal/non-verbal status of the patients (50). In addition, the included studies used various pain scale assessments, including OPS (24,(26)(27)(28)(29), CHEOPS (30,31), FLACC (6,9,19,(32)(33)(34), CHIPPS (35), pinprick at each dermatome (36), or a VAS (30), participating in heterogeneity. Even if all these assessments assess pain, they use different indicators (51).…”
Section: Discussionmentioning
confidence: 99%
“…The pain was evaluated using the Objective Pain Score (OPS) (24, 26-29), Children's Hospital of Eastern Ontario Pain Scale (CHEOPS) (30,31), Face, Legs, Activity, Cry, and Consolability (FLACC) (6,9,19,(32)(33)(34), Children and Infants Postoperative Pain Scale (CHIPPS) ( 35), pinprick at each dermatome (36), or a visual analog scale (30). When possible, the pain was evaluated as a continuous variable for comparisons between the two groups.…”
Section: Pain Evaluationmentioning
confidence: 99%
“…In different centers, various concentrations of different LAs are used, while general anesthesia is administered empirically or based on cardiovascular responses during the surgery without knowing the depth of anesthesia. Several studies have shown that some drugs can be used instead of opioids and anesthetics ( 3 - 6 ), and have also evaluated the effects of different LA agents on anesthetic requirements during CGEA using bispectral index (BIS) monitoring; the optimal combination and dose, however, have not been yet reported ( 4 , 5 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%